ERNICA guidelines for the management of rectosigmoid Hirschsprung’s disease - Kyrklund, Kristiina; Sloots, Cornelius E. J.; de Blaauw, Ivo; Bjørnland, Kristin; Rolle, Udo; Cavalieri, Duccio; Francalanci, Paola; Fusaro, Fabio; Lemli, Annette; Schwarzer, Nicole; Fascetti-Leon, Francesco; Thapar, Nikhil; et al. (Orphanet journal of rare diseases, 2020)
Hirschsprung's disease (HSCR) is a serious congenital bowel disorder with a prevalence of 1/5000. Currently, there is a lack of systematically developed guidelines to assist clinical decision-making regarding diagnostics and management. This guideline aims to cover the diagnostics and management of rectosigmoid HSCR up to adulthood. It aims to describe the preferred approach of ERNICA, the European Reference Network for rare inherited and congenital digestive disorders. Recommendations within key topics covering the care pathway for rectosigmoid HSCR were developed by an international workgroup of experts from 8 European countries within ERNICA European Reference Network from the disciplines of surgery, medicine, histopathology, microbiology, genetics, and patient organization representatives. Recommendation statements were based on a comprehensive review of the available literature and expert consensus. AGREE II and GRADE approaches were used during development. Evidence levels and levels of agreement are noted. Thirty-three statements within 9 key areas were generated. Most recommendations were based on expert opinion. In rare or low-prevalence diseases such as HSCR, there remains limited availability of high-quality clinical evidence. Consensus-based guidelines for care are presented.